FTIR Spectra of n-Octanol in Liquid and Solid States. (19th February 2014) - Vasileva, A.; Golub, P.; Doroshenko, I.; Pogorelov, V.; Sablinskas, V.; Balevicius, V.; Ceponkus, J.
Abstract : The investigation of the temperature dependence of FTIR spectrum of n-octanol in the temperature range from −150°C to 50°C is presented. The observed changes in the registered spectra during gradual heating of the sample were analysed. The structure transformation at the phase transition from solid to liquid phase is detected.